Utilization and Strengthening of Character through Digital Media in Learning to Write Descriptive Texts - Kurmalasari, Tety; Zaitun; Nerita; Abdulhajar, Encik; Irawan, Dody (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
Integrating local culture into language learning is a practical approach to enhancing students' writing skills while promoting positive character values and cultural identity. This study focuses on the utilisation and strengthening of character through digital media in learning to write descriptive texts by highlighting the Malay maritime tradition of the jong boat race as contextual learning material for elementary school students. The purpose of this study is to develop descriptive text writing competencies that incorporate traditional Malay culture, modern technology, and the principles of meaningful learning, thereby fostering the connection between new knowledge and students' existing experiences and knowledge. The method employed is a mixed-methods approach, combining quantitative and qualitative methods. The quantitative approach uses a pre-experimental one-class pretest-posttest design to measure the improvement of writing skills before and after learning. The qualitative approach is carried out through classroom observations, semi-structured interviews, and documentation to explore the experiences and responses of students and teachers. Digital media, including photos, short videos, and presentation applications, are used to help students observe, analyse, and describe the characteristics, materials, and processes of the Jong Boat Race. The results indicate that integrating cultural elements supported by digital visual sources and meaningful learning strategies can enhance students' descriptive vocabulary, sentence structure, emotional engagement, and depth of understanding. Furthermore, this approach encourages students to appreciate and preserve Malay maritime traditions, thereby enabling language learning to be integrated with cultural education. The study concluded that technology-enabled culture-based learning not only enriches students' language skills but also strengthens cultural awareness, making it a relevant and sustainable strategy for language education at the primary school level.